A critical review of outcomes of peer group mentoring and elements influencing its success and application to student placement supervisors. - Nisbet, Gillian; McAllister, Lindy (International Journal of Practice-based Learning in Health and Social Care, 2015)
Within the mentoring literature, peer group mentoring is emerging as an alternative approach to the traditional one-on-one experienced mentor-novice mentee model. The aim of this study was to examine the evidence base for peer group mentoring with a view to developing a sustainable peer group mentoring framework specifically for student placement supervisors within both the health and community sectors. A literature review was undertaken to determine models of peer group mentoring, elements contributing to their success and reported outcomes. The search strategy was intentionally broad to include papers outside of the health and community sectors. Eleven papers were located that met the inclusion criteria. Models of peer group mentoring broadly fell under three categories: peer led; experienced facilitator present with an active role; and experienced facilitator present in a supportive role. The success of peer group mentoring was influenced by structural elements of the programme, a focus on relationship building, and the learning environment. Outcomes included personal benefits to participants, educational gains, relationship development and productivity improvements. Based on this review, peer group mentoring appears to offer a novel approach to effectively and efficiently supporting and developing our student placement supervisors, ensuring quality learning experiences for our students.